PENGOLAHAN BIJI JAGUNG MENJADI CORNFUSE NATURAL CHOICE SEBAGAI ALTERNATIF MINUMAN SEHAT - Rajamuddin, Sintia; Pesik, Vena; Maronrong, Nabila Sanzabila; Permana, Dimas Ero; Towoliu, Benny Irwan (HOSPITALITI DAN PARIWISATA, 2025)
The growing public awareness of healthy lifestyles has led to a shift in consumption patterns,particularly in reducing the intake of caffeinated beverages such as coffee. The adverse effects ofcaffeine including sleep disturbances, anxiety, and dependency underscore the need for healthier andmore natural alternatives. This study aimed to develop Cornfuse Natural Choice, a functionalbeverage derived from sweet corn, formulated to resemble coffee in aroma, taste, and appearance, yetfree of caffeine. Corn was selected for its nutritional profile, including dietary fiber, B vitamins, andantioxidants, as well as its naturally pleasant flavor and consumer acceptance. The researchemployed a design-based approach, utilizing data collection methods such as experimentation,interviews, and organoleptic testing. A total of 13 respondents—comprising academics, students, thegeneral public, and industry practitioners—participated in evaluating the product’s sensory attributesand packaging. The production process involved stages of cleaning, drying, roasting, cooling,grinding, and packaging. Findings indicated that a 30-minute roasting period yielded the mostpreferred sensory characteristics, closely mimicking coffee while preserving corn's distinctive notes.Cornfuse Natural Choice demonstrates strong potential for commercialization as a nutritious,caffeine-free beverage alternative in the functional food and drink market.